Enhanced Student Class Attendance by Using Concept of Flipped Classroom Approach - Bipul Kumar Sarker (Journal of Social, Humanity, and Education, 2023)
Purpose: The absenteeism of students in the classroom at an education institute is the interventional issue for this study and the flipped classroom method is used to solve or minimize this issue. Methodology: This study was conducted on 100 (before and after) students of the 2020-21 session (Bangla, English, Philosophy, Mathematics and Statistics courses) of two reputed colleges in Dhaka City. The collected data were analyzed and compared using independent t-test methods, where instructional intervention was an independent variable, and class attendance and mid-term mark were considered dependent variables. Results: The results of this study show that the class attendance and mid-term exam mark of students in the two groups (flipped method and traditional method) are statistically significant at a 5% level of significance (class attendance t =15.54, p = 0.00, <0.05, mid-term exam mark, t =17.83, p = 0.00, <0.05). The classroom class attendance and mid-term exam mark for the students in the flipped method group (class attendance: mean score 89.62, mid-term exam mark: mean score 20.58) were significantly greater than that of the traditional method group (class attendance: mean score 49.22, mid-term exam mark: mean score 8.54). Limitations: In this study, only 100 students’ data was collected from two reputed colleges in Dhaka city, consequently the results obtained from this study may not represent the overall context. Contribution: These two statistical results indicate the flipped classroom approach is better than the traditional approach. Thus, applying flipped classroom model to teaching keeps students engaged in a variety of activities before/in/after class, increased learning interest, and reduces student absenteeism. Novelty: The method applied in this study has opened new horizons instead of the long-standing conventional idea in the field of education.